Examining Motivation and Perception of Visitors at Lekki Conservation Centre (LCC) in Nigeria - Arowosafe, Folusade C.; Tunde-Ajayi, Olalekan A.; Ojo, Bola D. (European Scientific Journal, ESJ, 2020)
People are driven to take up various actions due to motivation. The study examined the motivation and perception of visitors as well as examining the future behavioural intentions of the visitors at Lekki Conservation Centre (LCC), Lagos state, Nigeria. The study employed self-administered questionnaire to obtain information from the visitors. Random sampling method was used to select a total of 200 visitors involved in the survey. Data obtained were analyzed using Statistical Package for Social Sciences (SPSS 21) and results were presented descriptively and inferentially. Results obtained indicated that attractions such as canopy walkway, games served as pullattractions for the visitors to the site while adventure, sightseeing, relaxation and rest were highly ranked as push-motivations for the visitors to the site. The visitors also perceived the site experience as a satisfactory one while affirming they would revisit and recommend the site to other. Chi square analysis revealed a significant relationship between visitors’ motivation and perception (p=0.000). The site posed minimal challenges for visitation and as such is a good place to visit as it affords visitors an entertaining and satisfactory experience. Motivation study is important for tourist sites to improve their competitiveness in the market as it facilitates improvement of visitors’ satisfaction.